The 1918 Influenza Pandemic: Back to the Future? - Robert J. Unwin (Karger Publishers, 2021)
Background: It is just over a century since the 1918 flu pandemic, sometimes referred to as the "mother" of pandemics. This brief retrospective of the 1918 pandemic is taken from the viewpoint of the current SARS-CoV-2/COVID-19 pandemic and is based on a short lecture given during the 2021 Virtual Congress of the ERA-EDTA. Summary: This review summarizes and highlights some of the earlier pandemic's salient features, some parallels with today, and some potential learnings, bearing in mind that the flu pandemic occurred over 100 years ago at a time of major turmoil during the climax to WWl, and with limited medical expertise and knowledge, research facilities, or well-structured and resourced healthcare services. While there is little or no information on renal complications at the time, or an effective treatment, some observations in relation to COVID-19 and vaccination are included. Key Messages: Lessons are difficult to draw from 1918 other than the importance and value of non-pharmaceutical measures to limit viral transmission. While the economic impact of the 1918 pandemic was significant, as it is now with COVID-19, subsequent economic analysis has shown that protecting public health and preserving economic activity are not mutually exclusive. Both H1N1 and SARS-CoV-2 viruses are neurotropic and may cause chronically debilitating neurological diseases, including conditions such as encephalitis lethargica (still debated) and myalgic encephalomyelitis (chronic fatigue syndrome), respectively. Although coronavirus and influenza viral infections have some similarities, they are certainly not the same, as we are realising, and future infectious pandemics may still surprise us, but being "forewarned is forearmed."